INOVASI PENDIDIKAN AGAMA ISLAM DALAM MEMPROMOSIKAN NILAI-NILAI MODERASI BERAGAMA DI DAERAH EKS LOKALISASI - Munfiatik, Siti (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2024)
This research explores the promotion of religious moderation values ​​in the ex-local area of ​​Kampung Kajang, with a focus on innovative approaches in Islamic Religious Education (PAI). The method applied in this research is a descriptive qualitative research method. The informants in this research were Islamic Religious Education teachers, community leaders, and the millennial generation in the former localization area. The number of informants was 10 people, determined through the purposive sampling technique. This research was carried out in the Ex. Region. Localization of Kajang Village, South Sangatta. The research results show that the values ​​of moderation being promoted include respect for differences, interreligious dialogue, and participation in social activities, which are important for creating harmony amidst diversity. The people of Kampung Kajang show awareness of the importance of tolerance, although challenges in implementation still exist. Innovation in PAI plays a key role, where the integration of moderation values ​​in the curriculum needs to be adapted to the local context. It is hoped that the use of social media as a learning tool can increase the understanding of the younger generation. However, there are problems such as students' difficulties understanding the relevance of these values ​​and a lack of support from teachers. This research emphasizes the need for training for educators and collaboration between the community, educators and religious leaders to create an environment that supports the implementation of religious moderation values ​​through effective educational innovation.